MEMBANGUN KESADARAN HUKUM MASYARAKAT MELALUI MODEL PELATIHAN DAN PENYULUHAN - Sawaluddin Siregar; Dermina Dalimunthe; Syapar Alim Siregar (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to enhance legal awareness among the community through a participatory training and outreach model. The underlying issue addressed by this program is the low level of public understanding regarding legal rights and obligations, as well as the prevalence of rule violations due to limited legal knowledge. The program was implemented using a field-based approach, beginning with a needs analysis, followed by the development of relevant legal materials, and culminating in interactive training sessions and open public outreach activities. The methods employed included lectures, group discussions, case studies, and simple simulations to facilitate community understanding of common legal issues encountered in daily life, such as land disputes, debt agreements, and family-related matters. The results indicate a significant improvement in community legal awareness, as reflected in active participation during discussions and the participants’ ability to identify appropriate legal solutions in accordance with applicable regulations. Furthermore, the program contributed to strengthening the relationship between the community and village officials as legal facilitators. Through the training and outreach activities, community members demonstrated increased confidence in addressing legal issues and a stronger commitment to complying with legal norms. This program demonstrates that training and outreach models can serve as effective instruments in fostering legal awareness and promoting a law-abiding culture at the local level.